Avaliação do uso isolado e combinado de oxidantes sob radiação UV-C para degradação de microcontaminantes orgânicos em efluente sanitário terciário em meio ácido (pH 3) - Santos, Gabrielly Machado dos (2025)
During the Covid-19 pandemic, there was an increase in the consumption of drugs such as colchicine (COL) and nitazoxanide (NTZ), which resulted in an increase in their concentrations in aquatic matrices. Therefore, studies evaluating the application of advanced oxidative processes as a complementary step to the conventional processes used in a sewage treatment plant are necessary for the degradation of these compounds and other organic microcontaminants. Therefore, the present work used the multivariate optimization tool - Mixture Planning (PM) to evaluate the influence of the concentration (0-500 μM) of the oxidants hydrogen peroxide (H2O2), persulfate (S2O82-) and hypochlorite (OCl-) on the simultaneous degradation of COL and NTZ (325 nM, each) in tertiary sanitary effluent in acidic medium (pH 3.0) and under UV-C radiation. Applying the PM, it was possible to verify that H2O2 (500 μM) alone presented a superior performance in the simultaneous degradation of the target compounds when compared to the combined oxidants. Kinetic experiments were conducted under optimized conditions, in addition to control experiments (photolysis and oxidation in the dark). Under optimized conditions, the target compounds showed a degradation above 92% after 20 minutes of irradiation. This result demonstrates the improved efficiency of the process, due to the generation of hydroxyl radicals (HO•). In contrast, the action of the oxidant in the dark resulted in only 17% degradation, while photolysis reached 30% in the same experimental period. Mass spectrometry allowed the identification of four transformation products of NTZ after the application of the UV-C/ H2O2 process, two of which are new in the literature. These products, together with those of COL and other components of the matrix, which were not identified, did not demonstrate toxic effects in the effluent, taking into account the phytotoxicity parameters in Lactuca Sativa and the cytotoxic ones in Azospirillum Brasilense and UFU-13. However, cytotoxic effects were observed in Saccharomyces Cerevisiae. These results show the importance of optimizing the operational conditions to determine which of them positively affect the degradation and to define the best condition that provides the maximum degradation efficiency; prerequisites for an expansion of the treatment scale.